2014
DOI: 10.1152/jn.00697.2013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of optic flow on the control of heading and target egocentric direction during steering toward a goal

Abstract: Although previous studies have shown that people use both optic flow and target egocentric direction to walk or steer toward a goal, it remains in question how enriching the optic flow field affects the control of heading specified by optic flow and the control of target egocentric direction during goal-oriented locomotion. In the current study, we used a control-theoretic approach to separate the control response specific to these two cues in the visual control of steering toward a goal. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Firstly, the improvements of steering profiles along with higher RR in flow fields are consistent with studies reporting that the addition of flow assists heading control (Li and Warren 2002, Wilkie and Wann 2002, Wilkie and Wann 2003, Li, Stone et al 2011, Li and Cheng 2011a, Li and Cheng 2013, Li and Niehorster 2014. Secondly, our results are in line with who showed that, despite perceiving heading accurately, participants can sometimes produce poor performance in a steering-towards-a-target tasks.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Firstly, the improvements of steering profiles along with higher RR in flow fields are consistent with studies reporting that the addition of flow assists heading control (Li and Warren 2002, Wilkie and Wann 2002, Wilkie and Wann 2003, Li, Stone et al 2011, Li and Cheng 2011a, Li and Cheng 2013, Li and Niehorster 2014. Secondly, our results are in line with who showed that, despite perceiving heading accurately, participants can sometimes produce poor performance in a steering-towards-a-target tasks.…”
Section: Discussionsupporting
confidence: 92%
“…Li et al also discovered that with richer optic flow, participants could better correct heading errors caused by pseudo-random perturbations (Li, Stone et al 2011). In a more recent experiment, Li et al confirmed that both visual direction and optic flow are used in steering but humans react faster to visual direction (Li and Niehorster 2014). In summary, a number of studies confirmed that both visual direction and optic flow are used for self-locomotion.…”
Section: Chapter Three -Study 2: a Test Of Steering In Optic Flow Expmentioning
confidence: 90%
See 2 more Smart Citations
“…G. Harris & Carré, 2001;W. H. Warren, Kay, Zosh, Duchon, & Sahuc, 2001; J. M. Harris & Bonas, 2002;Li & Cheng, 2013;Li & Niehorster, 2014). In simulated locomotion and steering tasks, the role of target egocentric direction, is normally not considered when a strong egocentric reference frame is missing.…”
Section: Differential Effects Of Simulated Gaze Rotationsmentioning
confidence: 99%